PERENCANAAN ARSITEKTUR ENTERPRISE MENGGUNAKAN TOGAF ADM PADA DISPORA KOTA SALATIGA - Adimas Agil Pangestu (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The Office of Youth and Sports (DISPORA) of Salatiga City is a government organization that focuses on increasing sports achievement and youth potential. Continuity of business and IT strategy is a harmonious and continuous process. DISPORA itself currently has not fully implemented an integrated information system in all existing fields. Enterprise architectural planning can integrate current systems with future systems. The method used is TOGAF ADM by conducting interviews and observations. TOGAF ADM is a method that consists of steps in designing an enterprise architecture for a company or organization. The stages carried out are only up to the Opportunities and Solutions phase. The results found in this study are the need for continuity between fields so that business process activities run as expected. The results of this study are expected to produce a blueprint for the proposed IS / IT to become the basis for the strategic business process activities of the Salatiga City Youth and Sports Service.